Posteromedial hyperactivation during episodic recognition among people with memory decline: findings from the WRAP study. - Nicholas, Christopher; Okonkwo, Ozioma; Bendlin, Barbara; Oh, Jennifer; Asthana, Sanjay; Rowley, Howard; Hermann, Bruce; Sager, Mark; Johnson, Sterling; Nicholas, Christopher R; Okonkwo, Ozioma C; Bendlin, Barbara B; et al. (Brain Imaging & Behavior, 2015)
Episodic memory decline is one of the earliest preclinical symptoms of AD, and has been associated with an upregulation in the BOLD response in the prodromal stage (e.g. MCI) of AD. In a previous study, we observed upregulation in cognitively normal (CN) subjects with subclinical episodic memory decline compared to non-decliners. In light of this finding, we sought to determine if a separate cohort of Decliners will show increased brain activation compared to Stable subjects during episodic memory processing, and determine whether the BOLD effect was influenced by cerebral blood flow (CBF) or gray matter volume (GMV). Individuals were classified as a "Decliner" if scores on the Rey Auditory Verbal Learning Test (RAVLT) consistently fell ≥ 1.5 SD below expected intra- or inter-individual levels. FMRI was used to compare activation during a facial recognition memory task in 90 Stable (age = 59.1) and 34 Decliner (age = 62.1, SD = 5.9) CN middle-aged adults and 10 MCI patients (age = 72.1, SD = 9.4). Arterial spin labeling and anatomical T1 MRI were used to measure resting CBF and GMV, respectively. Stables and Decliners performed similarly on the episodic recognition memory task and significantly better than MCI patients. Compared to Stables, Decliners showed increased BOLD signal in the left precuneus on the episodic memory task that was not explained by CBF or GMV, familial AD risk factors, or neuropsychological measures. These findings suggest that subtle changes in the BOLD signal reflecting altered neural function may be a relatively early phenomenon associated with memory decline.